Edukasi Dampak Negatif Konsumsi Minuman BOBA Terhadap Kesehatan Di SMPN 16 Kota Jambi - M.Dody Izhar; Ummi Kalsum; Rizalia Wardiah (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2022)
Boba is a contemporary drink that is popular in Indonesia, especially among teenagers. Boba drinks contain high levels of sugar and calories, because they are part of the Sugar Sweetened Beverage (SSB) group or sweetened drinks that generally contain sweeteners in the form of high fructose corn syrup / HFCS (55% fructose, 45% glucose) or sucrose (50% fructose, 50% glucose). Therefore, socialization related to the dangers of boba consumption was carried out which aims to minimize the incidence of illness due to consumption of contemporary drinks at SMP N 16 Jambi City. The method used in this activity is educational counseling on the negative impact of boba drinks on 40 students at SMP Negeri 16 Jambi City. The result of this activity is that students know better that boba drinks contain high sugar and have risks to health such as digestive disorders, obesity, dental and oral health. This activity is known through evaluation with the question and answer method and the message chain game method. There were 2 monitoring and evaluation sessions in this community service activity, the first was a debriefing from the resource person asking 5 questions, then those who could answer regarding the dangers of boba drink were given a reward. And the second session made two game groups consisting of 4 students each. Then each representative was given a clue or sentence by the speaker, which would then be followed up by whispering it to the next student. Thus, monitoring and evaluation in PPM activities can be carried out properly, and all students are more aware of the dangers of drinking boba.Keywords : Dangers of Boba, Contemporary Drinking, Sugar Sweetened Beverage (SSB)